The Complex Roles of DNA Repair Pathways, Inhibitors, Hyperthermia, and Contact Inhibition in Cell Cycle Halts - Ahmed, Muhammad B.; Alghamdi, Abdullah A.A.; Islam, Salman Ul; Ahsan, Haseeb; Lee, Young Sup (Mini Reviews in Medicinal Chemistry, 2023)
The cell cycle has the capacity to safeguard the cell’s DNA from damage. Thus, cell cycle arrest can allow tumor cells to investigate their own DNA repair processes. Cancer cells become extremely reliant on G1-phase cyclin-dependent kinases due to mutated oncogenes and deactivated tumor suppressors, producing replication stress and DNA damage during the S phase and destroying checkpoints that facilitate progression through the S/G2/M phase. DNA damage checkpoints activate DNA repair pathways to prevent cell proliferation, which occurs when the genome is damaged. However, research on how cells recommence division after a DNA lesion-induced arrest is insufficient which is merely the result of cancer cells’ susceptibility to cell cycle arrest. For example, defects in the G1 arrest checkpoint may cause a cancer cell to proliferate more aggressively, and attempts to fix these complications may cause the cell to grow more slowly and eventually die. Defects in the G2-M arrest checkpoint may enable a damaged cell to enter mitosis and suffer apoptosis, and attempts to boost the effectiveness of chemotherapy may increase its cytotoxicity. Alternatively, attempts to promote G2-M arrest have also been linked to increased apoptosis in the laboratory. Furthermore, variables, such as hyperthermia, contact inhibition, nucleotide shortage, mitotic spindle damage, and resting phase effects, and DNA replication inhibitors add together to halt the cell cycle. In this review, we look at how nucleotide excision repair, MMR, and other variables, such as DNA replication inhibitors, hyperthermia, and contact inhibition, contribute to the outlined processes and functional capacities that cause cell cycle arrest.
Keywords: CDKs